Edukasi dan Demonstrasi Kompres Jahe Dan Serai Sebagai Terapi Komplementer Dalam Penanganan Nyeri Asam Urat Pada Lansia Di Desa Suka Sari - Sewifa, Nadila Yulan; Pirmansyah, Arif; Putri, Elia; Dinanti , Dita; Putri , Reni Dwi; Susanti, Meri Epriana; Diniarti, Fiya (Universitas Dehasen Bengkulu, 2026)
Gout, or hyperuricemia, is a metabolic disorder whose prevalence continues to rise worldwide. In 2020, the global prevalence reached 55.8 million cases with an age-standardized rate of 659.3 per 100,000 population. In Indonesia, the prevalence of gout diagnosed by healthcare professionals is reported at 7.3%, indicating that it remains a significant community health problem. Gout is characterized by joint pain, inflammation, and functional limitations that interfere with daily activities. Non-pharmacological approaches using natural ingredients offer a safe, affordable, and easily accessible alternative for community-based management. This community engagement program aimed to improve public knowledge and skills in managing gout-related pain through education and hands-on demonstration of warm compresses made from ginger and lemongrass. The activity included health education on risk factors, symptoms, and early management of gout, followed by a live demonstration on preparing and applying ginger–lemongrass warm compresses. The results showed an improvement in participants’ understanding and their ability to independently perform the compress technique. Participants reported feelings of warmth, relaxation, reduced joint stiffness, and increased awareness of natural household ingredients as complementary therapy. This program proved effective in enhancing community awareness and self-care practices in non-pharmacological gout management. Similar community-based programs are recommended to be implemented continuously to strengthen public empowerment in utilizing safe, simple, and practical natural remedies.